ECOLOGICAL ASPECTS OF CHEMICAL AND PHYSICO-CHEMICAL FORTIFICATION OF SOILS (Web of Teachers: Inderscience Research, 2024)
This article covers the ecological aspects of chemical and physico-chemical reinforcement of grunts and the methods of chemical and physico-chemical reinforcement of grunts.